The death penalty as state crime: who can kill? - Finley, Laura L. (Routledge, 2024)
"This book offers a new perspective on the death penalty in the US, examining capital punishment as state crime or state-produced harm. It addresses the death penalty, showing how the state not only authorizes a system and a practice that tortures human beings, but is also aware of its deep flaws and chooses not to address them. Building on the vast literature on state crime together with case examples, and interviews with activists seeking to abolish the death penalty, this book offers a new and innovative critique of state punishment in the US. It draws on a range of issues and topics such as arbitrariness, inadequate counsel, racial bias, mental illness, innocence, conditions on death row, the protocols, and the equipment used for executions. It emphasizes the need for abolition of the death penalty and highlights efforts being made to do so, with a focus on successful elements of abolition campaigns. The Death Penalty as State Crime is essential reading for all those engaged with capital punishment, human rights, and state crime, and will be of interest to criminologists, sociologists, legal scholars and political scientists alike"--